Comparative Analysis of Islamic Commercial Banks and Sharia Business Units in Indonesia - Cedrich Zakhariah; Hesniati Hesniati (ITB AAS INDONESIA Surakarta, 2022)
This study focuses on explaining the comparison between Islamic Commercial Banks and Islamic Business Units in Indonesia through financial risk which includes liquidity risk consisting of Liquid Assets to Total Assets, Financing to Deposits, and Cash to Deposits ratios. Then through credit risk which is represented by the ratio of Non-Performing Financing and operational risk which is represented by the ratio of Cash to Income. In addition, the size of the banking company is used as a control variable in this study. This study uses all Islamic banking operating in Indonesia from 2016 to 2020 with the purposive sampling method in obtaining the sample. As a result, the sample in this study consists of 14 Islamic Commercial Banks and 20 Sharia Business Units. The results are shown in testing this research data state that there are significant differences between Islamic Commercial Banks and Islamic Business Units in Indonesia from 2016 to 2020 when viewed from the ratio of Liquid Assets to Total Assets and Cost to Income. However, in the ratio of Financing to Deposit, Cash to Deposit, and Non-Performing Financing, it is shown that there is no significant difference between the Islamic Commercial Banks and the Sharia Business Units.